ALDH2/SIRT1 Contributes to Type 1 and Type 2 Diabetes-Induced Retinopathy through Depressing Oxidative Stress. (23rd October 2021) - He, Mengshan; Long, Pan; Chen, Tao; Li, Kaifeng; Wei, Dongyu; Zhang, Yufei; Wang, Wenjun; Hu, Yonghe; Ding, Yi; Wen, Aidong
Abstract : Clinical observations found vision-threatening diabetic retinopathy (DR) occurs in both type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) patients, but T1DM may perform more progressive retinal abnormalities at the same diabetic duration with or without clinical retinopathy. In the present study, T1DM and T2DM patients without manifestations of DR were included in our preliminary clinical retrospective observation study to investigate the differentiated retinal function at the preclinical stage. Then, T1DM and T2DM rat models with 12-week diabetic duration were constructed to explore the potential mechanism of the discrepancy in retinal disorders. Our data demonstrated T1DM patients presented a poor retinal function, a higher allele frequency for ALDH2GA/AA, and a depressed aldehyde dehydrogenase 2 (ALDH2) activity and silent information regulator 1 (SIRT1) level, compared to T2DM individuals. In line with this, higher amplitudes of neurovascular function-related waves of electroretinograms were found in T2DM rats. Furthermore, the retinal outer nuclear layers were reduced in T1DM rats. The levels of retinal oxidative stress biomarkers including total reactive oxygen species, NADPH oxidase 4 and mitochondrial DNA damage, and inflammatory indicators covering inducible/endothelial nitric acid synthase ratio, interleukin-1, and interleukin-6 were obviously elevated. Notably, the level of retinal ALDH2 and SIRT1 in T1DM rats was significantly diminished, while the expression of neovascularization factors was dramatically enhanced compared to T2DM. Together, our data indicated that the ALDH2/SIRT1 deficiency resulted in prominent oxidative stress and was in association with DR progression. Moreover, a differentiating ALDH2/SIRT1 expression may be responsible for the dissimilar severity of DR pathological processes in chronic inflammatory-related T1DM and T2DM.